1976
DOI: 10.2134/agronj1976.00021962006800010016x
|View full text |Cite
|
Sign up to set email alerts
|

An Aseptic Mist Chamber System: A Method for Measuring Root Processes of Peas1

Abstract: Although plants have been grown with their roots in mist chambers and sterile nutrient solutions, these methods have not been combined to provide a system which permits rapid changes in the gaseous composition of an aseptic rhizosphere. The objectives of this study were to design a mist chamber system which would withstand heat sterilization, maintain an aseptic rhizosphere, permit rapid gaseous exchange without altering rootwater relationships, and permit the measurement of morphological and physiological roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Experimental designs range from stagnant or flowing solutions with or without aeration (HYDROPONIC-ONLY) and agar matrices (e.g. Jones and Darrah, 1993;Marschner et al, 1987;Neumann and Romheld, 1999;Strehmel et al, 2014) to fog-boxes or mist chambers (AEROPO-NIC) (Clayton and Lamberton, 1964;Quintana et al, 2008;Smucker and Erickson, 1976) to percolating systems with sand, glass beads, perlite or vermiculite (SEMI-HYDROPONIC) applied for mechanical stabilization (Neumann et al, 2009;Neumann and Römheld, 2007 and references therein). The recently developed transparent soil (Nafion) (Downie et al, 2014) may represent an interesting alternative to the commonly used matrices in SEMI-HYDROPONIC studies as the transparent properties are highly compatible with a wide range of root and microbe targeting imaging techniques.…”
Section: Hydroponic Culture Based Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental designs range from stagnant or flowing solutions with or without aeration (HYDROPONIC-ONLY) and agar matrices (e.g. Jones and Darrah, 1993;Marschner et al, 1987;Neumann and Romheld, 1999;Strehmel et al, 2014) to fog-boxes or mist chambers (AEROPO-NIC) (Clayton and Lamberton, 1964;Quintana et al, 2008;Smucker and Erickson, 1976) to percolating systems with sand, glass beads, perlite or vermiculite (SEMI-HYDROPONIC) applied for mechanical stabilization (Neumann et al, 2009;Neumann and Römheld, 2007 and references therein). The recently developed transparent soil (Nafion) (Downie et al, 2014) may represent an interesting alternative to the commonly used matrices in SEMI-HYDROPONIC studies as the transparent properties are highly compatible with a wide range of root and microbe targeting imaging techniques.…”
Section: Hydroponic Culture Based Approachesmentioning
confidence: 99%
“…These setups easily allow the user to easily control the atmosphere in the root zone (ranging from aerobic to completely anoxic) and can (if recycling is not wanted) continuously renew the nutrient solution while still keeping the required volume of nutrient solution manageable. Early studies mainly relied on custommade designs (Clayton and Lamberton, 1964;Graham, 1991;Smucker and Erickson, 1976), while most recent studies have used commercial systems (Quintana et al, 2008;Yang et al, 2004). Compared to the classical HYDROPONIC-ONLY system, AEROPONICs are rarely used and often AEROPONIC growth is combined with HYDROPONIC-ONLY exudation sampling (Jandova et al, 2015) or root tissue extraction (Yang et al, 2004;Zimmermann et al, 2003).…”
Section: Hydroponic Culture Based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The system can conserve water and energy. It uses nutrient rich-water recirculation hence; system offers lower water and energy inputs per unit growing area (Ritter et al 2001;Farran and Mingo-Castel 2006;Lester 2014) and offer a means of controlling the atmosphere in the root zone and provide a method for measuring of cell division and physiological responses of plant (Smucker and Erickson 1976). The adoption of the system would be economical, beneficial and valuable for local farmers to perform agricultural activities.…”
Section: Overview and Concept Of The Aeroponics Systemmentioning
confidence: 99%
“…It is clear there is wide potential for creating experimental designs in aeroponics to explore exudation behaviors under various moisture regimes. Yet, few studies have reported the collection of aeroponic droplets for exudate analysis (31)(32)(33), and to the best of our knowledge, there are no studies utilizing aeroponics to study the effect of drought on root exudation.…”
Section: Introductionmentioning
confidence: 99%